Inoperable scalp cutaneous angiosarcoma: Complete response after definitive external beam radiation therapy – brachytherapy association. (February 2022) - Le Roy, Charlotte; Le Péchoux, Cécile; Alapetite, Claire; Bahleda, Ratislav; Ngo, Carine; Honoré, Charles; Faron, Matthieu; Le Cesne, Axel; Mir, Olivier; Haie-Meder, Christine; Chargari, Cyrus; Levy, Antonin
Summary: Effective treatments are scarce in non-operable scalp cutaneous angiosarcoma patients. Curative-intent definitive sequential IMRT and plesiobrachytherapy allowed complete response with limited side effect in two elder patients. This could represent a non-invasive therapeutic option for patients with locally advanced presentation.